Cellular receptors for foot and mouth disease virus. (2009)
Foot-and-mouth disease virus (FMDV), the prototype member of the Aphthovirus genus, is a single-stranded, positive-sense RNA genome virus, which affects many domestic livestock cloven-hoofed animals, causing substantial lost of milk in dairy cattle, reduction in the growth rate of meat animals, among others. It has been shown that the virus can enter to the cells using different pathways; the main one binding integrins via the clathrin-mediated endocytosis pathway, trafficking throughout the acidified endocytic vesicles, where its capsid rapidly dissociates, resulting in the release of the RNA genome, and the second one using heparan sulfate in which FMDV enters to the cells using the caveola-mediated endocytosis pathway and that caveolae can associate and traffic with endosomes. Different integrins had been involved as FMDV receptors (alphavbeta1, alphavbeta3, alpha5beta1, alphavbeta6, alphavbeta8); this review will try to resume the basic information about FMDV receptors from the last years to the present and will resume the most important in vitro and in vivo studies to elucidate the role of this receptor on the infection.